Manajemen Risiko dengan Metode FMEA di Instalasi Gawat Darurat Rumah Sakit Kuwait - Bisri Mustofa; Ekayana S. Paranita; Tatan Sukwika (Management Studies and Entrepreneurship Journal (MSEJ), 2023)
The Emergency Room (IGD) is part of the most vital service unit in helping to save the lives of patients who experience medical emergencies when they are first admitted to the hospital. Given the many potential hazards and risks that can cause work accidents, work-related illnesses, sentinel events and other unexpected events, efforts are needed to reduce or control these risks, so that all human resources in the hospital can avoid work-related accidents or diseases. Risk management actions are taken to respond to various risks in business activities or organizations. This risk management activity is carried out before the risk occurs so that it is an anticipatory action that can be taken and makes a plan that can be used if the risk arises so as to reduce negative impacts and avoid large losses. This study aims to analyze risk events, risk assessment, and causes of occupational safety and health (K3) risks for nurses at the Kuwait General Hospital Emergency Room. The approach used in this research is descriptive qualitative method. While the population of this study were all nurses in the Emergency Room at the Kuwait General Hospital. The sample method used is probability sampling. The sampling method or technique above was carried out using simple random sampling. Research data analysis uses the Failure Mode and Effect Analysis (FMEA) method for risk analysis, in calculating the Risk Priority Number (RPN) and making a list of critical risks by calculating the ratio of the total RPN value divided by a number of risks. The results of the analysis show that there are five stages of service activities that pose Occupational Health and Safety (K3) risks to nurses working in the Emergency Room at the Kuwait General Hospital. The five risks in the activity stage are getting there, arriving, being seen, receiving treatment, and leaving. It was also found that ten factors of the three occupational safety and health (K3) risks for nurses that arise from the process of service activities in the emergency room.